He pukenga wai, he nohoanga tāngata. He nohoanga tāngata, he putanga kōrero: The Whanganui River, People, Knowledge, Technology and Place - Baron, Gabriel (Auckland University of Technology, 2020)
Many indigenous cultures are facing the struggle of language revitalisation. The need for constant effort and contribution has resulted in assessment and experiments in use of modern technologies. This research seeks to explore how emerging technologies can aid in the process of revitalising a tribal variation, within the iwi (tribe) of Te Atihaunui-ā-pāpārangi, located in the Whanganui area in the North Island of New Zealand. The main research questions asked how technology can support the revitalisation of te reo o Whanganui (Whanganui tribal variation). Additional supporting questions focused on the current utilisation of digital resources to promote the Māori language and to justify the positive effects of technology for language revitalisation and cultural promotion. An Indigenous framework with Kaupapa Māori research theory was developed and a Whanganui methodology was constructed to guide the research to produce authentic Whanganui data. The participants were all active and respected members of Te Atihaunui-ā-pāpārangi, with areas of expertise in the Whanganui tribal variation and tikanga Whanganui (Whanganui protocols). The findings revealed interesting and, at times, contradictory attitudes of using technology to transmit, promote and create tribal knowledge. The role the Te Atihaunui-ā-pāpārangi diaspora plays in cultural and language transmission was an unexpected theme and it is argued that all members of the iwi can actively contribute in the retention of Whanganui’s cultural heritage. Further research on community development initiatives and supporting technologies can aid in connecting all groups of Te Atihaunui-ā-pāpārangi.
Keywords: Te Awa Tupua; Whanganui; Whanganui River; Gabriel Baron; Technology; Te reo o Whanganui; Tikanga Whanganui; Whanganui Methodology; Te Atihaunui-ā-pāpārangi